Parental Use of Multimodal Cues in the Initiation of Joint Attention as a Function of Child Hearing Status. Issue 5 (2nd July 2020) - Gabouer, Allison; Oghalai, John; Bortfeld, Heather
ABSTRACT: In the current study we examine how hearing parents use multimodal cuing to establish joint attention with their hearing ( n = 9) or deaf ( n = 9) children during a free-play session. The deaf children were all candidates for cochlear implantation who had not yet been implanted, and each hearing child was age-matched to a deaf child. We coded parents' use of auditory, visual, and tactile cues, alone and in different combinations, during both successful and failed bids for children's attention. Although our findings revealed no clear quantitative differences in parents' use of multimodal cues as a function of child hearing status, secondary analyses revealed that hearing parents of deaf children used shorter utterances while initiating joint attention than did hearing parents of hearing children. Hearing parents of deaf children also touched their children twice as often throughout the play session than did hearing parents of hearing children. These findings demonstrate that parents differentially accommodate the specific needs of their hearing and deaf children in subtle ways to establish communicative intent.